Penggunaan model pembelajaran tipe Student Teams Achievement Division (STAD) dalam pembelajaran psikologi - Nurfaizah, Rosania (Maliki Interdisciplinary Journal, 2023)
Learning is one factor that greatly influences the survival of all people, learning is not limited by age. When someone learns something new, it is usually difficult to accept it. If in this learning a child gets the right learning, ease of accepting new things will form, and vice versa. The learning model provided by the teacher or lecturer can trigger a feeling of boredom and laziness in students, boredom in students in learning will reduce or even eliminate the effectiveness of the learning process. Therefore, the selection of learning methods must be considered, so that they can lead to good benefits for students. Research with cooperative learning method variables and student teams achievement division variables has been widely studied, including the effect of the cooperative learning model type student achievement division. In this literature review article, the results of these studies will be described, with the aim of being able to help students master something after carrying out the learning process.